Analisis Pengaruh Utang Luar Negeri Pemerintah terhadap Pertumbuhan Ekonomi Indonesia (Periode 1980-2019) - Dinar Rafikhalif; Dyah Nirmalawati (Universitas Negeri Padang, 2021)
This study aims to analyze the effect of government foreign debt on economic growth in the period 1980-2019 in the long and short term by using time series data analysis using the Error Correction Model (ECM). Other independent variables analyzed are investment and Labor Force Participation Rate (TPAK). The results show that the government's foreign debt has a positive and significant impact on economic growth. The value of the elasticity coefficient of economic growth to the government's foreign debt is 4.86 in the long term and 2.47 in the short term. The investment variable and LFPR also show a positive and significant effect in the long and short term, except for the investment variable which has no significant effect in the short term. The ECT coefficient in the short term produced is -0.360222 indicating the speed of adjustment of economic growth towards equilibrium is 36.02% per year